Gamma-ray shielding features of lithium borate glass doped with Ag, Cd and Zn using Phy-X program - Mario César Pérez Chávez; Janet Alejandra Elías Ángel; Christian Gómez-Solís; Ramón Castañeda-Priego; Héctor René Vega Carrillo; Modesto Antonio Sosa Aquino; Miguel Ángel Vallejo Hernández (Boletín de la Sociedad Española de Cerámica y Vidrio, 2023)
Lithium borate glasses doped with three transition metals: Ag, Cd and Zn were prepared with the melt-quenching method. Dopants concentrations were (Li2B4O7)(100−x) (Zn[NO3]2, CdN2O6, AgNO3) (x = 0%, 1%, 5%). Doped glasses were analyzed and their shielding features were determined. The XRD measurements show the amorphous state of the glasses. Fluorescence analysis shows the characteristic emission of Ag, Cd and Zn and their enhancement is explained. UV–vis spectra were recorded in the interval 200–900 nm, and show the peaks belonging to the plasmon of the three transition metals. The optical energy band gaps were calculated using the Tauc's plot model; also, the refractive index was calculated. Additionally, density (ρ) and molar volume (Vm) were calculated as part of the characterization of the samples. In order to determine the shielding features against gamma-rays the mass attenuation coefficient (μ/ρ)(E), the half value layer (HVL(E)) and the Effective Atomic Number (Zeff(E)) for photons from 0.015 to 15 MeV using the Phy-X program. Resumen: Los vidrios de borato de litio dopados con tres metales de transición: Ag, Cd y Zn se prepararon con el método de enfriamiento por fusión. Las concentraciones de dopantes fueron (Li2B4O7)(100 − x) (Zn[NO3]2, CdN2O6, AgNO3) (x = 0%, 1%, 5%). Se analizaron los vidrios dopados y se determinaron sus características de protección. Las mediciones de XRD muestran el estado amorfo de las gafas. El análisis de fluorescencia muestra la emisión característica de Ag, Cd y Zn y se explica su mejora. Los espectros UV-vis se registraron en el intervalo 200-900 nm y muestran los picos pertenecientes al plasmón de los tres metales de transición. Los huecos de las bandas de energía óptica se calcularon utilizando el modelo de gráfico de Tauc; además, se calculó el índice de refracción. Además, la densidad (ρ) y el volumen molar (Vm) se calcularon como parte de la caracterización de las muestras. Para determinar las características de blindaje contra los rayos gamma, el coeficiente de atenuación de masa (μ/ρ)(E), la capa de valor medio (HVL(E)) y el Número Atómico Efectivo (Zeff(E)) para fotones de 0.015 a 15 MeV usando el programa Phy-X.